Sea vessel type selection via an integrated VAHP-ANP methodology for high-speed public transportation in Bosphorus - Gumus, Alev Taskin; Yilmaz, Gokhan (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The transportation planning phases are generally examined in three groups, according to their contents, constant and variable factors, time dimensions, financial costs and decision-making levels: Strategic, tactical and operational levels. Network design and development, terminal capacity and location determination, marketplace selection and vessel fleet and working-power planning are problems of strategic level planning. We are interested in sea vessel type selection to efficient vessel fleet planning in this study. This paper deals with issues related to the selection of right sea vessel type for short and medium distances in Bosphorus and proposes an integrated methodology for this process. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bosphorus; Public transportation; Seaway; VAHP; ANP; HIERARCHY PROCESS METHOD; RANKED VOTING SYSTEM; MODEL; DEA; UNITS; Computer Science; Engineering; Operations Research & Management Science